Data and image compression tools and techniques - Held, Gilbert (John Wiley & Sons, 1996)
Now covering both data and image compression, this edition keeps pace with technology. It includes new coverage of fax and compression methods, as well as a range of compression-related tools to display, print, and convert images from one format to another. Reviews of the four most popular archive creation and compression performing programs are also included. Two disks include the coding in BASIC and C for many of the compression algorithms in the book.